2020
DOI: 10.1111/jocs.14579
|View full text |Cite
|
Sign up to set email alerts
|

The effect of patient obesity on extracorporeal membrane oxygenator outcomes and ventilator dependency

Abstract: Objective The effect of body habitus for patients who require extracorporeal membrane oxygenation (ECMO) support has not been well‐studied and may provide insight into patient survival and outcomes. We sought to determine if there is a correlation of body mass index (BMI) with ECMO outcomes. Methods A retrospective chart review was performed for patients who required any form of ECMO support at our institution between 2012 and 2016. Time variables (overall hospital length of stay, intensive care, and ventilato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 11 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…Genore et al reported that there was no difference in mortality and other significant complications in patients with different weight classes when stratified between venovenous ECMO and venoarterial ECMO [31]. is finding was similar to the conclusion of a much more extensive review of ELSO registry by Kon et al in 2017, where he reported that venovenous ECMO was not associated with worse outcomes or complications than venoarterial ECMO for ARDS [38].…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Genore et al reported that there was no difference in mortality and other significant complications in patients with different weight classes when stratified between venovenous ECMO and venoarterial ECMO [31]. is finding was similar to the conclusion of a much more extensive review of ELSO registry by Kon et al in 2017, where he reported that venovenous ECMO was not associated with worse outcomes or complications than venoarterial ECMO for ARDS [38].…”
Section: Discussionmentioning
confidence: 52%
“…All studies that were included in this analysis showed that there was no added mortality risk in obese patients when treated with ECMO therapy as compared to nonobese patients. e primary outcome compared in our analysis was "successful weaning from ECMO," and this outcome was reported in the main article or supplementary material of Cho et al [27], Dalia et al [28], Eunmi et al [29], Genore et al [31], and Salna et al [32].…”
Section: Findings and Resultsmentioning
confidence: 99%
See 3 more Smart Citations